2012
DOI: 10.1103/physrevc.85.051603
|View full text |Cite
|
Sign up to set email alerts
|

Probing elastic and inelastic breakup contributions to intermediate-energy two-proton removal reactions

Abstract: The two-proton removal reaction from 28 Mg projectiles has been studied at 93 MeV/u at the NSCL. First coincidence measurements of the heavy 26 Ne projectile residues, the removed protons and other light charged particles enabled the relative cross sections from each of the three possible elastic and inelastic proton removal mechanisms to be determined. These more final-state-exclusive measurements are key for further interrogation of these reaction mechanisms and use of the reaction channel for quantitative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We now discuss and estimate the degree to which this approximation may overestimate the diffraction-stripping cross sections in these relatively light residue reactions; the dominant two-nucleon stripping mechanism will be unaffected. For two-proton knockout from 28 Mg, calculations using the present no-recoil approach reproduce the relative strengths of stripping and diffraction-stripping mechanisms within experimental errors [7]; the experimental and theoretical diffraction-stripping branching ratios were found to be b exp = 31(16)% and b th = 37.4%. Here, the recoil corrections for the light 12 C projectile will be considerably larger.…”
Section: Recoil Effectsmentioning
confidence: 59%
See 1 more Smart Citation
“…We now discuss and estimate the degree to which this approximation may overestimate the diffraction-stripping cross sections in these relatively light residue reactions; the dominant two-nucleon stripping mechanism will be unaffected. For two-proton knockout from 28 Mg, calculations using the present no-recoil approach reproduce the relative strengths of stripping and diffraction-stripping mechanisms within experimental errors [7]; the experimental and theoretical diffraction-stripping branching ratios were found to be b exp = 31(16)% and b th = 37.4%. Here, the recoil corrections for the light 12 C projectile will be considerably larger.…”
Section: Recoil Effectsmentioning
confidence: 59%
“…A feature of this model description is that the removal cross sections involve only elastic interactions of the projectile residues with the target but sums of contributions from both elastic and inelastic interactions of one or both nucleons with the target [6]. New data, for the sd-shell nucleus 28 Mg and the 28 Mg(−2p) reaction, have quantified these different contributions experimentally [7] and have confirmed that the relative importance of these different processes to the cross sections are consistent with the predictions of the eikonal dynamical model. This has provided an important additional test of the reaction model.…”
Section: Introductionmentioning
confidence: 99%
“…The HiRA array covered polar angles (ϑ) from 9 • to 56 • and for a given value of ϑ up to 40% of the azimuthal angles were covered. A correction for the limited azimuthal acceptance within the ϑ range was applied following our previous work [16].…”
Section: Methodsmentioning
confidence: 99%
“…2(f) shows the experimental partial cross sections extracted for states in 22 Mg compared to the cross sections calculated using the USD TNAs. Previous work on two-nucleon knockout [4][5][6]34] has found a ratio of approximately 0.5 between experimental and theoretical in- (8), and 0.62(11), respectively. Interestingly, the experimental cross section for the 2 + 1 state is 0.31(11) mb while the theoretical prediction is 0.117 mb.…”
Section: (20) Kev [11]mentioning
confidence: 99%